Long non-coding RNAs in drug resistance across the top five cancers: Update on their roles and mechanisms - Yue Shi; Joseph Adu-Amankwaah; Qizhong Zhao; Xin Li; Qianxue Yu; Aisha Bushi; Jinxiang Yuan; Rubin Tan (Heliyon, 2024)
Cancer drug resistance stands as a formidable obstacle in the relentless fight against the top five prevalent cancers: breast, lung, colorectal, prostate, and gastric cancers. These malignancies collectively account for a significant portion of cancer-related deaths worldwide. In recent years, long non-coding RNAs (lncRNAs) have emerged as pivotal players in the intricate landscape of cancer biology, and their roles in driving drug resistance are steadily coming to light. This comprehensive review seeks to underscore the paramount significance of lncRNAs in orchestrating resistance across a spectrum of different cancer drugs, including platinum drugs (DDP), tamoxifen, trastuzumab, 5-fluorouracil (5-FU), paclitaxel (PTX), and Androgen Deprivation Therapy (ADT) across the most prevalent types of cancer. It delves into the multifaceted mechanisms through which lncRNAs exert their influence on drug resistance, shedding light on their regulatory roles in various facets of cancer biology. A comprehensive understanding of these lncRNA-mediated mechanisms may pave the way for more effective and personalized treatment strategies, ultimately improving patient outcomes in these challenging malignancies.